Social Change Communication and Message Production of Transgender Individuals Through TikTok Social Media Activities - Jovanni Enralin Silalahi; Maya Arina Pramudita (Formosa Journal of Social Sciences (FJSS), 2024)
Social media TikTok is chosen by LGBT individuals as an appropriate medium to voice their existence so that they can be accepted by the broader society, at least to gain recognition & equal basic rights as ordinary human beings. Some TikTok users known to be LGBT adherents are no longer ashamed to open up and admit their orientation to the public. This study uses a qualitative content analysis method. Content analysis provides new insights, increases the researcher's understanding of a particular phenomenon, or informs practical actions. TikTok influencers who show personal activity and uploads their personal life as an LGBT person, specifically transgender. Using TikTok to upload daily life videos is a new diplomacy approach in communicating the lifestyle they adhere to and representing the concerns felt by many LGBT adherents. Every individual is born with their own circumstances, and by appreciating and accepting their condition, they will be happy and spread happiness to those around them